Chemerin-9 stimulates migration in rat cardiac fibroblasts in vitro - Yamamoto, Atsunori; Sagara, Ayumi; Otani, Kosuke; Okada, Muneyoshi; Yamawaki, Hideyuki (European journal of pharmacology, 2021)
Since chemerin is an adipocytokine whose concentration in blood increases in the subjects with various cardiac diseases, chemerin may be involved in pathogenesis of cardiac diseases. In the present study, we examined the effects of chemerin-9, an active fragment of chemerin, on functions of cardiac fibroblasts, which are involved in pathophysiology of cardiac diseases. Primary cardiac fibroblasts were enzymatically isolated from adult male Wistar rats. Migration of cardiac fibroblasts was measured by a Boyden chamber assay and a scratch assay. Phosphorylation of Akt and extracellular signal-regulated kinase (ERK) was measured by Western blotting. Reactive oxygen species (ROS) production was measured by 2′,7′-dichlorodihydrofluoresein staining. Chemerin-9 significantly stimulated migration in cardiac fibroblasts. Chemerin-9 significantly stimulated phosphorylation of Akt and ERK as well as ROS production. An Akt pathway inhibitor, LY294002, an ERK pathway inhibitor, PD98059, an antagonist of chemokine-like receptor 1 (CMKLR1), 2-(α-Napththoyl) ethyltrimethylammonium iodide, or an antioxidant, N-acetyl-L-cysteine prevented the migration induced by chemerin-9. In summary, we for the first time revealed that chemerin-9 stimulates migration perhaps through the ROS-dependent activation of Akt and ERK via CMKLR1 in cardiac fibroblasts. It is proposed that chemerin plays a role in the pathogenesis of cardiac diseases.